What to do when you worry too much : a kid's guide to overcoming anxiety - Huebner, Dawn ("What to do" guides for kids, 2006)
"Teaches school-age children cognitive-behavioral techniques to reduce and overcome anxiety, fears, and worry, through writing and drawing activities and self-help exercises and strategies. Includes introduction for parents"--Provided by publisher.